2014
DOI: 10.1111/lang.12067
|View full text |Cite
|
Sign up to set email alerts
|

The Perception of Fluency in Native and Nonnative Speech

Abstract: Where native speakers supposedly are fluent by default, nonnative speakers often have to strive hard to achieve a nativelike fluency level. However, disfluencies (such as pauses, fillers, repairs, etc.) occur in both native and nonnative speech and it is as yet unclear how fluency raters weigh the fluency characteristics of native and nonnative speech. Two rating experiments compared the way raters assess the fluency of native and nonnative speech. The fluency characteristics were controlled by using phonetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(55 citation statements)
references
References 62 publications
6
48
0
1
Order By: Relevance
“…This applies to raters who are experienced in teaching and testing L2 speakers (Kormos and Dénes, 2004) as well as to untrained native or nonnative speakers (Bosker et al, 2013;Pinget et al, 2014;Rossiter, 2009). These findings are corroborated by two more experimental studies in which speech samples are phonetically manipulated (Munro & Derwing, 1998;Bosker, Quené, Sanders & De Jong, 2014). Munro and Derwing (1998, Exp. 2) reduced the speech rate of the recordings of Mandarin speakers of English as a second language and native speakers of English and found that native listeners were negatively affected by the manipulation of speech rate.…”
Section: Two Factors: Features Of the Speech And Rater Backgroundsupporting
confidence: 66%
See 1 more Smart Citation
“…This applies to raters who are experienced in teaching and testing L2 speakers (Kormos and Dénes, 2004) as well as to untrained native or nonnative speakers (Bosker et al, 2013;Pinget et al, 2014;Rossiter, 2009). These findings are corroborated by two more experimental studies in which speech samples are phonetically manipulated (Munro & Derwing, 1998;Bosker, Quené, Sanders & De Jong, 2014). Munro and Derwing (1998, Exp. 2) reduced the speech rate of the recordings of Mandarin speakers of English as a second language and native speakers of English and found that native listeners were negatively affected by the manipulation of speech rate.…”
Section: Two Factors: Features Of the Speech And Rater Backgroundsupporting
confidence: 66%
“…Munro and Derwing (1998, Exp. 2) reduced the speech rate of the recordings of Mandarin speakers of English as a second language and native speakers of English and found that native listeners were negatively affected by the manipulation of speech rate. Bosker et al (2014) conducted an experiment in which the number and length of pauses in native and non-native speech was manipulated. Natives were rated more fluent and speech with no pauses was also rated as more fluent than speech with short and long pauses, respectively.…”
Section: Two Factors: Features Of the Speech And Rater Backgroundmentioning
confidence: 99%
“…While exemplar models and probabilistic models of perception can deal with the effect via direct associations between fast speech and the presence of fast-speech processes, abstractionist models would assume increased cognitive load due to more difficult mapping between signal and representations. Together with other recent studies on external influences on the implicit perception of speaking rate (Bosker & Reinisch, 2015;Bosker et al, 2016), evidence appears to accumulate that normalization for speaking rate may in fact be explained at multiple levels of processing.…”
Section: Discussionmentioning
confidence: 99%
“…Bosker and Reinisch (2015) showed that carrier sentences that were spoken by a nonnative speaker led to more Blong vowelr esponses than when the carrier was spoken by a native speaker. That is, despite an overall match in long-term spectral properties, duration, and number of realized segments, nonnative speech was perceived as faster than native speech in an implicit rate normalization task.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been recognized that prosodic properties of the acoustic context do not merely serve as background noise, but rather influence subsequent speech perception [1,2]. For instance, the perception of an ambiguous Dutch vowel midway between short /ɑ/ and long /a:/ may be shifted towards the perception of long /a:/ by presenting it in a context sentence with a fast speech rate [3].…”
Section: Introductionmentioning
confidence: 99%